The Hermeneutics of the Qur’an: A Comparative Study of Fazlur Rahman and Nasr Hamid Abu Zayd - Mohammad Muslih; Ahmad Hisyam Syamil; Amir Reza Kusuma (al-Bunyan: Interdisciplinary Journal of Qur'an and Hadith Studies, 2025)
This study examines the hermeneutical approaches of Fazlur Rahman and Nasr Hamid Abu Zayd in interpreting the Qur’an, highlighting their methodological innovations and epistemological divergences. Fazlur Rahman’s "Double Movement" theory seeks to bridge historical and contemporary contexts by extracting universal moral principles from Qur’anic injunctions, maintaining the text’s divine authority while advocating for contextual application. In contrast, Nasr Hamid Abu Zayd employs a linguistic-historical hermeneutic, treating the Qur’an as a "cultural product" shaped by socio-historical dynamics, thereby emphasizing its textuality over traditional theological frameworks. While Rahman’s approach aligns with Islamic moral-theological continuity, Abu Zayd’s secular-linguistic methodology, influenced by Western hermeneutics and post-structuralism, challenges classical exegetical norms, raising concerns about the Qur’an’s sacredness and normative authority. The study critically evaluates both models, revealing tensions between modernization and Islamic epistemological foundations, and underscores the necessity of grounding hermeneutical innovations within a tawḥīd-centric framework to preserve the Qur’an’s integrity as divine guidance.